2017
DOI: 10.17072/2078-7898/2017-4-643-657
|View full text |Cite
|
Sign up to set email alerts
|

Health status as a factor of labor activity of the retirement-age population

Abstract: Обзор мирового экономического и социального положения, 2007 год xx Обзор мирового экономического и социального положения, 2007 год Общий обзор xxi Общий обзор xxvii Обеспеченность медицинским персоналом требуемой квалификацииОдной из насущных проблем как в развивающихся, так и в развитых странах яв ляется отсутствие достаточного количества квалифицированных медицинских кадров. В развивающихся странах, особенно в странах с низким уровнем дохода, нехватка квалифицированных медицинских работников уже заметна и бу… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A population survey conducted in 2013 by the Institute of Social Analysis and Forecasting of the RANEPA (Russian Presidential Academy of National Economy and Public Administration) [9][10] showed that the reasons for stopping work to reach retirement age are poor health and fatigue, since it is they that determine the ability of an elderly person to work. At the same time, a number of sociological and medical studies [11][12] show that working pensioners are healthier. Thus, in the scientific literature there are two points of view regarding the health of working pensioners.…”
Section: Introductionmentioning
confidence: 99%
“…A population survey conducted in 2013 by the Institute of Social Analysis and Forecasting of the RANEPA (Russian Presidential Academy of National Economy and Public Administration) [9][10] showed that the reasons for stopping work to reach retirement age are poor health and fatigue, since it is they that determine the ability of an elderly person to work. At the same time, a number of sociological and medical studies [11][12] show that working pensioners are healthier. Thus, in the scientific literature there are two points of view regarding the health of working pensioners.…”
Section: Introductionmentioning
confidence: 99%